Long-term PAH accumulation after bud break in L. leaves in a polluted environment - Alfani, a; Nicola, F; Maisto, G; Prati, M (Atmospheric Environment, 2005)
The dynamics of polycyclic aromatic hydrocarbon (PAH) concentrations in the leaves of Quercus ilex L. for 16 months after bud break (May 2001–September 2002) were studied at a polluted site in the urban area of Naples by comparison to the dynamics at a control site in the Vesuvius National Park. Twenty-seven PAHs were extracted by sonication and quantiﬁed by GC-MS. Total PAH concentrations in the leaves sampled at the urban site showed a considerable increase from bud break, with the highest values during the winter (about 3-fold greater than the initial value) and a subsequent decrease, unlike the control site. The control site exhibited PAH concentrations one order of magnitude lower than the urban site. At the urban site, the medium molecular weight PAHs, amounting to 72% of the total, appear responsible for the temporal trend, while the low and high molecular weight PAHs (respectively, 10% and 18%) exhibited only narrow variations over time. At the control site, the low, medium and high molecular weight PAHs contributed similarly to the total concentrations (32%, 31% and 37%, respectively); the low molecular weight PAHs showed the widest temporal variations. Carcinogenic PAHs showed a dynamic at the urban site comparable to that shown by the total PAHs. At the control site dibenzo(a,h)anthracene exhibited concentrations higher than at the urban site
Keywords: air contamination; carcinogenic pahs; pah dynamics; pah leaf accumulation; polycyclic aromatic hydrocarbons

Long-term PAH accumulation after bud break in L. leaves in a polluted environment - Alfani, a; Nicola, F.; Maisto, G.; Prati, M. (Atmospheric Environment, 2005)
The dynamics of polycyclic aromatic hydrocarbon (PAH) concentrations in the leaves of Quercus ilex L. for 16 months after bud break (May 2001–September 2002) were studied at a polluted site in the urban area of Naples by comparison to the dynamics at a control site in the Vesuvius National Park. Twenty-seven PAHs were extracted by sonication and quantiﬁed by GC-MS. Total PAH concentrations in the leaves sampled at the urban site showed a considerable increase from bud break, with the highest values during the winter (about 3-fold greater than the initial value) and a subsequent decrease, unlike the control site. The control site exhibited PAH concentrations one order of magnitude lower than the urban site. At the urban site, the medium molecular weight PAHs, amounting to 72% of the total, appear responsible for the temporal trend, while the low and high molecular weight PAHs (respectively, 10% and 18%) exhibited only narrow variations over time. At the control site, the low, medium and high molecular weight PAHs contributed similarly to the total concentrations (32%, 31% and 37%, respectively); the low molecular weight PAHs showed the widest temporal variations. Carcinogenic PAHs showed a dynamic at the urban site comparable to that shown by the total PAHs. At the control site dibenzo(a,h)anthracene exhibited concentrations higher than at the urban site
Keywords: air contamination; carcinogenic pahs; pah dynamics; pah leaf accumulation; polycyclic aromatic hydrocarbons